Ravindranath Tagore rachnavali/ Baikunth ka potha, Swargiya prahasan - Tagore, Ravindra Nath; Edited by Indra Nath Chaudhury (New Delhi Sasta Sahitya Mandal, 2012)
Baikunth Ka Potha , Swargiya Prahasan (Play)
Keywords: Hindi play; Noble prize winner Ravindra Nath Tagore